ESG and dividend policy: Evidence from ASEAN-5 countries - Ismillah, Nisa Hamdu; Faisal, Muhammad (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
This study aims to investigate the effect of Environmental, Social, and Governance (ESG) on dividend policy. ESG disclosure is measured using the Refinitiv Eikon database's ESG Score, and dividend policy is measured using the Dividend Payout Ratio (DPR). Purposive sampling was used to obtain 115 samples of non-financial companies listed on the ASEAN-5 Countries Stock Exchange from 2017 to 2021. The sample companies originated from the ASEAN-5 countries. These countries include Indonesia, Malaysia, Singapore, Philippines, and Thailand. The results suggest that ESG has a positive effect on dividend policy. Companies with higher ESG scores are more likely to have suitable dividend policies, as companies that disclose ESG indicate a high level of transparency and a low risk of information asymmetry. This study provides empirical evidence to support the implementation of ESG disclosure in numerous nations, particularly the ASEAN-5. This study provides empirical incentives for company managers to implement ESG disclosure and its components. The relationship between ESG and its components and dividend policy in ASEAN-5 countries has yet to be investigated.